Two essays in information disclosure and initial public offerings in Latin America (2016)
"This dissertation has an introduction and two chapters. In the first chapter I study the prospectus presented during the initial public offering using a statistical approach of natural language processing. I also explore firm and market determinants of tone. Particularly, I am interested in the interaction between CEO and underwriters, the ones in charge of writing the prospectus... In the second chapter I study the relation between uncertainty in tone used in the prospectus and IPO performance in Latin America. I set up a situation in which a potential investor is collecting information to decide about an initial public offering. More specific, I study the complementary vs substitute idea between governance traits and uncertainty tone". Tomado del resumen